Faktor-Faktor Yang Mempengaruhi Financial Distress Dengan Firm Size Sebagai Variabel Moderasi - Meliana Tania, Henryanto Wijaya (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The objective of this research is to examine the influence of liquidity, leverage, operating capacity and operating cash flow that being moderated by firm size to financial distress on the manufacturing companies listed on the IDX in 2017-2019. The sample was selected by using purposive method and there are 16 companies that were selected as samples. This research uses the moderated regression analysis (MRA) method to analyze data using the Eviews program version 11. The results show that liquidity, leverage and firm size have a positive and significant effect to financial distress. However, operating capacity and operating cash flow do not have a significant effect on financial distress. This study also shows that firm size weakens the effect of leverage on financial distress. However, liquidity, operating capacity and operating cash flow, which are moderated by the firm size, have no effect to financial distress. The implication of this study is to provide suggestions for companies in predicting financial distress conditions. The earlier the signs of bankruptcy are known, the better company management to immediately find solutions of the problems.